Ethnohistory as a research strategy for traditional architecture history: A systematic literature review - Khamdevi, Muhammar; Sudradjat, Iwan (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The history of Indonesian traditional architecture has not yet addressed the history of architecture itself; instead, it has only addressed national and regional universal history as a backdrop or ancestry. Furthermore, the sources mainly relied on Western paradigm-adhering written documents and literature rather than empirical sources from a specific cultural community, particularly oral traditions. As a result, the significance of historical context for the evolution of Indonesian architecture has diminished somewhat. Indeed, anthropology, archaeology, and history have long used ethnohistory as a research methodology. Furthermore, traditional architecture has been mentioned in these studies. How does one go about researching the history of traditional architecture using ethnohistory? The objectives of this research are to identify research trends on this topic as well as to discover novelty as a new direction for future studies. This study employs a systematic literature review (SLR) method to descriptively analyze a big dataset and examine the content of primary data selected from publications between 2013 and 2023. It indicates how very promising the research trend is for architecture science. Furthermore, this study develops three research focuses, approaches, implications and constraints in light of the data gathered and examined.